2005
DOI: 10.1172/jci26662
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stone disease

Abstract: About 5% of American women and 12% of men will develop a kidney stone at some time in their life, and prevalence has been rising in both sexes. Approximately 80% of stones are composed of calcium oxalate (CaOx) and calcium phosphate (CaP); 10% of struvite (magnesium ammonium phosphate produced during infection with bacteria that possess the enzyme urease), 9% of uric acid (UA); and the remaining 1% are composed of cystine or ammonium acid urate or are diagnosed as drug-related stones. Stones ultimately arise b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
567
2
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(595 citation statements)
references
References 123 publications
(75 reference statements)
11
567
2
15
Order By: Relevance
“…The association of heterozygous PHIII mutations to idiopathic calcium oxalate urolithiasis reported by Monico et al 21 presents an exciting hypothesis, in particular in conjunction with the observations from this family, although the low rate of urolithiasis observed in our parental cohort may question this conclusion. 27 Our findings are of particular relevance as mutation screening is usually halted as soon as causative mutations have been identified in a first gene. In the light of our working hypothesis that in some cases the PH phenotype may be modulated by mutations in other genes affecting glyoxylate metabolism, complete sequencing of all known causative genes should be considered, notably in those patients who lack a second causative mutation or those with an atypical presentation.…”
Section: Discussionmentioning
confidence: 85%
“…The association of heterozygous PHIII mutations to idiopathic calcium oxalate urolithiasis reported by Monico et al 21 presents an exciting hypothesis, in particular in conjunction with the observations from this family, although the low rate of urolithiasis observed in our parental cohort may question this conclusion. 27 Our findings are of particular relevance as mutation screening is usually halted as soon as causative mutations have been identified in a first gene. In the light of our working hypothesis that in some cases the PH phenotype may be modulated by mutations in other genes affecting glyoxylate metabolism, complete sequencing of all known causative genes should be considered, notably in those patients who lack a second causative mutation or those with an atypical presentation.…”
Section: Discussionmentioning
confidence: 85%
“…Many unilateral obstructions are caused by nephrolithiasis, with calcium oxalate and calcium phosphate stones accounting for 80% of these. The lifetime incidence of nephrolithiasis is 12% in men and 6% in women [1]. Urological intervention secondary to obstruction is necessary when stones exceed 7mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Each heterozygous change segregated from his mother and father, respectively. The second patient was described as a 38-year-old man, with recurrent (calcium phosphate) renal stones since the age of 25 and hyperkalaemia, hypercalciuria, suppressed PTH and elevation of 1,25(OH) 2 vitamin D. He also had bi-allelic mutations, a c.1226T>C, p.L409S change inherited from his mother and the c.428_430del; p.E143del mutation inherited from his father. Metabolic studies in both patients confirmed reduced enzyme function with undetectable activity of CYP24A1 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The oldest known stone (from approximately 4800 BCE) was found in an Egyptian grave in 1901 1 . Today, renal stones pose a significant public health problem, with lifetime risk of forming a stone exceeding 5% in women and 12% in men 2 . The direct and indirect costs are substantial, with the annual cost in the United States estimated to be in excess of $5 billion 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation